2012
DOI: 10.1016/j.chemosphere.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Particles in swimming pool filters – Does pH determine the DBP formation?

Abstract: The formation was investigated for different groups of disinfection byproducts (DBPs) during chlorination of filter particles from swimming pools at different pH values and the toxicity was estimated. Specifically, the formation of the DBP group trihalomethanes (THMs), which is regulated in many countries, and the non-regulated haloacetic acids (HAAs) and haloacetonitriles (HANs) were investigated at 6.0 ≤ pH ≤ 8.0, under controlled chlorination conditions. The investigated particles were collected from a hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Similar tests have been used in other studies that investigated the potential of formation of NCl 3 (Schmalz et al, 2011), THM and HAA in swimming pool water (Kanan and Karanfil, 2011), and THM, HAN and HAA from particles from a swimming pool (Hansen et al, 2012).…”
Section: Dbp Formation Testsmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar tests have been used in other studies that investigated the potential of formation of NCl 3 (Schmalz et al, 2011), THM and HAA in swimming pool water (Kanan and Karanfil, 2011), and THM, HAN and HAA from particles from a swimming pool (Hansen et al, 2012).…”
Section: Dbp Formation Testsmentioning
confidence: 79%
“…Studies on drinking water chlorination at pH <7 reported decrease in THMs concentration while HAA formation increases or decreases depending on the source water (Bougeard et al, 2008;Liang and Singer, 2003). A recent study with particles of anthropogenic origin found that THM and HAA formations were reduced by decreasing pH while HAN formation increased with decreasing pH (Hansen et al, 2012).…”
mentioning
confidence: 99%
“…The analyses were performed as previously published in (Hansen et al, 2012a). In brief free chlorine was quenched by adding ammonium chloride solution to the vials before they were filled head-space-free with sample.…”
Section: Analysis Of Trihalomethanes and Haloacetonitrilesmentioning
confidence: 99%
“…When DBP precursors are in the water a potential method improvement suggested in literature is to lower the pH in order to reduce the formation of trihalomethanes (THMs) (Kristensen et al, 2007). However, recent studies reported an increased formation of the more toxic DBP group, haloacetonitriles (HANs), when decreasing the pH (Hansen et al, 2012a;Hansen et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Modern living requires the usage of myriads of xenobiotics including pesticides, pharmaceuticals, personal care products, and solvents that find their way into the natural environment (Antoniou et al, 2013;de la Cruz et al, 2011;Esperanza et al, 2007;Hansen et al, 2010;Hansen et al, 2012;Marfil-Vega et al, 2011). Though found at small concentrations (thus are commonly known as micropollutants) they can still have adverse effects in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%